Physiological Changes of Bamboo (Fargesia yunnanensis) Shoots During Storage and the Related Cold Storage Mechanisms - Yu, Lixia; Pei, Jialong; Zhao, Yihe; Wang, Shuguang (Frontiers in Plant Science, 2021)
The mechanisms for physiological senescence in bamboo shoots after harvest remain unclear. This study investigated physiological changes in Fargesia yunnanensis shoots during storage at different temperatures. The relationship between morphological and physiological changes in bamboo shoots during storage was also analyzed. The results show that cold storage can reduce weight loss, browning, respiration rates, and sugar degradation in bamboo shoots; decrease related enzymatic activities; and inhibit the increase in lignin and cellulose content. The quality of bamboo shoots declines more during the first 3d after harvesting than it does during subsequent periods. The increase in the degree of lignification and fibrosis is the main reason for senescence and for the decline in quality of bamboo shoots after harvest. The bamboo shoots under RT conditions began browning during the third 3d of storage, with a browning rate of 688gkg−1 even in the upper parts; the increase in shoot browning degrees significantly decreased the quality. Low temperatures had better inhibitory effects on browning than they did on lignification and fibrosis. Nonstructural carbohydrates in bamboo shoots are degraded and flow into sheath and shoot respiration, phenols, and shoot fibrosis and lignification at room temperature, but only flow into sheath respiration, shoot fibrosis, and lignification at cold temperature. Soluble protein and free amino acids are primarily distributed into shoot and sheath respiration and into phenols at room temperature, but that process is well inhibited at cold temperature. Bamboo shoots, once removed from cold storage, should be consumed rapidly because enzyme activity recovers quickly. This research provides new theoretical information on the preservation of bamboo shoots.